(untitled) (Community Based Medical Journal, 2013)
Pemphigus vulgaris is a cutaneous blistering disorder affecting mainly middle aged adult and is rarely observed in pregnancy and also below the age of 30 years. A 27 years old lady with 7 months pregnancy reported to Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka with oral and cutaneous lesions suggestive of pemphigus vulgaris. Tzanck smear, histological examination and direct immunofluorescence study confirmed the diagnosis and the case showed improvement with only oral steroid. The patient delivered a normal healthy child without complications. No clinical relapse was found after delivery and follow up period of six months. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14188 Community Based Medical Journal Vol.2(1) 2013 66-68